The ameliorating effects of Bushen Tiaoxue Granules and Kunling Wan on impaired angiogenesis and endometrial receptivity in rats following controlled ovarian hyperstimulation. (3rd October 2019) - Lv, Bo‐Yang; Sun, Hao‐Yu; Li, Quan; Zhang, Hao‐Lin; Pan, Chun‐Shui; Yan, Li; Fan, Jing‐Yu; Li, Dong; Han, Jing‐Yan
Abstract: Objective: To investigate the effects of Bushen Tiaoxue Granules and Kunling Wan, the two Chinese medicines, on vascular dysfunction and the impairment of endometrial receptivity caused by controlled ovarian hyperstimulation and its underlying mechanism. Methods: Female Sprague Dawley rats with regular estrous cycle were enrolled and given Bushen Tiaoxue Granules or Kunling Wan by gavage for 12 days, and then, controlled ovarian hyperstimulation model was induced. We assessed endometrial microvessels, endometrial blood flow, levels of estradiol and progesterone in serum, vascular endothelial growth factor A upstream molecules estrogen and progesterone receptors in the endometrium, and pregnancy outcome. Results: Pre‐treatment of Bushen Tiaoxue Granules or Kunling Wan increases endometrial blood flow of controlled ovarian hyperstimulation rats, up‐regulates vascular endothelial growth factor A and microvessels, improves the endometrial morphology of controlled ovarian hyperstimulation rats during implantation, decreases the super physiological concentration of estradiol and progesterone in serum, and increases the expression of vascular endothelial growth factor A upstream molecules estrogen and progesterone receptors in the endometrium. In addition, Bushen Tiaoxue Granules or Kunling Wan elevates the lysophosphatidic acid receptor 3 that participates in vascularization and increases the expression of leukemia inhibitory factor through up‐regulating the expression of p53 in the endometrium, ultimately affecting pregnancy outcome. Conclusion: This study demonstrated Bushen Tiaoxue Granules or Kunling Wan as a potential strategy for prevention of impairment in angiogenesis and endometrial receptivity induced by controlled ovarian hyperstimulation.